Logics of career choice - concept and results of an approval-sensitive career guidance workshop - Mutlu, Sevil; Ziegler, Birgit; Granato, Mona (Frontiers in Psychology, 2024)
To manage the transition to work after compulsory schooling, young people need to learn about different occupations, explore their own interests, skills, and values, make career-related decisions, and develop a vocational identity (Neuenschwander, 2020). However, following the CC-theory (Gottfredson, 1981), we assume that young people have already narrowed down their spectrum of acceptable occupations and limited their career aspirations when they engage in school-based career orientation programs. A process that begins in early childhood influenced by their social environment and usually takes place unconsciously (Gottfredson, 2005). This forms the basis of the study, which focuses on career orientation interventions, taking into account the need for social approval among young people. We present first results of an intervention study on a newly developed approval-sensitive career orientation workshop "Logic of Career Choice" to confront youngsters explicitly with this topic. We examine the extent to which this workshop can stimulate students to think about unreflective aspects of their career decisions and to go into action. The analyses and results reported are based on a sample of n = 1236 students, including the treatment group of n = 766 and the control group of n = 470 students. Validation results from confirmatory factor analyses indicate that the new measurement instruments used are reliable. The six constructs of interest here relate to the (1) relevance of social approval, (2) feeling of autonomy, (3) interest in career choice, (4) reflection of needs, (5) intention to act, and (6) reported career choice activities. The hypotheses regarding (1) relevance of social approval and the (2) feeling of autonomy can be partially confirmed. The scales (4) reflection of needs and (5) intention to act show parallel developments in the treatment group and the control group, leading to the rejection of the workshop's effect. The constructs (3) interest in career choice and (6) retrospectively reported activities regarding career choice show effects. Interest in career choice decreases significantly more in the treatment group than in the control group, but the treatment group reports significantly more retrospective career choice activities. The results are discussed in terms of their scientific and practical implications.